Development of RSI-MA Based Expert Advisor with Money Management Optimization for GBP/USD Trading on Weltrade Swap-Free Account in MetaTrader 5 - Ginting, Lukas Destria Putra; Rahman, Haikal; Siregar, Zulkarnain (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This research develops an Expert Advisor (EA) based on Relative Strength Index (RSI) and Moving Average (MA) indicators with a money management strategy for trading GBP/USD on a swap-free account in MetaTrader 5. The strategy was tested in two different time frame scenarios (M30 and H1) with parameter optimization. This study employs the Research and Development method, analyzing data through backtesting and real-time testing. EA performance evaluation involved performance metrics such as win ratio, profit factor, drawdown, and recovery factor. Test results indicate that the M30 scenario is more optimal for short-term implementation, while the H1 scenario excels in long-term testing. Descriptive statistical analysis and T-tests revealed no significant difference between backtesting and real-time testing results for profit and total trades, but a significant difference for the balance variable. Overall, the developed EA shows good potential for adaptive automated trading strategies, especially on swap-free accounts.